Community Participation in Implementation of 4 Pillars of Sustainable Tourism in Janti Tourist Village, Klaten - Putri Arum Maheswari; Fulia Aji Gustaman (UIN Sunan Gunung Djati, 2024)
Tourism is a dynamic industry that significantly contributes to global economic growth by creating jobs and increasing income for both communities and governments. This study aims to analyze community participation in implementing the four pillars of sustainable tourism in Janti Tourism Village, Klaten Regency. Employing a qualitative approach, data were collected through interviews, observations, and analysis of relevant literature, including journals, books, and official documents. The data were then analyzed through three stages: data condensation, data presentation, and conclusion drawing or verification. The findings indicate that Janti Tourism Village has successfully evolved into a well-managed tourism destination by integrating community participation with sustainable tourism principles. The community plays an active role as tourism managers, cultural heritage preservers, and environmental stewards, facilitated through training programs, socialization efforts, and regular meetings. Additionally, community members have access to village meetings and performance reporting forums, ensuring their voices are heard in decision-making processes. The study confirms that Janti Tourism Village has effectively implemented the four pillars of sustainable tourism—sustainable management, socio-economic development, cultural preservation, and environmental conservation. These aspects are well-integrated within the village’s tourism development framework. However, further improvements are needed to enhance community engagement and optimize the benefits of sustainable tourism.